ANALISIS TEORITIK MODEL PEMBELAJARAN BERLATAR ISU-ISU KONTROVERSIAL DI PERGURUAN TINGGI - Suryanto, Suryanto; Salim, Nur (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2015)
The purpose of the study is to be achieved to find a theoretical learning model of controversial issues background, as a model for strengthening the scientific body of knowledge PKN subject in Higher Education. The early stages of this research is to find the basic concept as a model of scientific / theoretical model of learning PKN background controversial issues. This is a descriptive study, the research describes the social phenomena (learning background controversial issues). The approach used is qualitative. The main conclusions obtained are: the discovery of the basic concepts of scientific models/theoretical model of controversial issues background in Higher Education, which includes: (a) philosophical foundation, (b) theoretical basis of learning, (c) sociological grounding, (d) juridical basis, and (e) psychological foundation.Keyword: citizenship competencies, controversial issues